Myeloid-Derived Suppressor Cells Alleviate Renal Fibrosis Progression via Regulation of CCL5-CCR5 Axis - Qiu, Yue; Cao, Yirui; Tu, Guowei; Li, Jiawei; Su, Ying; Fang, Fang; Zhang, Xuepeng; Cang, Jing; Rong, Ruiming; Luo, Zhe (Frontiers in Immunology, 2021)
Background: Renal fibrosis is inevitable in all progressive chronic kidney diseases (CKDs) and represents a serious public health problem. Immune factors contribute to the progression of renal fibrosis. Thus, it is very possible that immunosuppression cells, such as myeloid-derived suppressor cells (MDSCs), could bring benefits to renal fibrosis. Herein, this study investigated the anti-fibrotic and reno-protective effect of MDSCs and the possible mechanisms. Methods: Murine and cell models of unilateral ureter obstruction (UUO) renal fibrosis were used. Bone marrow-induced MDSCs and granulocyte–macrophage colony stimulating factor (GM-CSF) were pretreated before surgery. Kidney weight, pathological injury, extracellular matrix deposition and epithelial-mesenchymal transition progression were examined. TGF-β1/Smad/Snail signaling pathway involvement was investigated through western blotting and qPCR. Accumulation of MDSC, CD4+ T cell, regulatory T (Treg), and T helper 1 (TH1) cell accumulation, and CCL5 and CCR5 expression level in MDSCs and non-MDSCs were evaluated using flow cytometry. Results: In vitro- and in vivo-induced MDSCs significantly ameliorated UUO-induced tubulointerstitial fibrosis, inhibited the TGF-β1/Smad/Snail signaling pathway, and enhanced MDSC and Treg infiltration in the kidney, while downregulating the TH1 cells. Both in vitro and in vivo experiments confirmed CCL5 elevation in the two MDSC-treated groups. Conclusion: In vitro- and in vivo-induced MDSCs alleviated renal fibrosis similarly through promoting the CCL5–CCR5 axis interaction and TGF-β1/Smad/Snail signaling pathway inhibition. Our results indicate an alternative treatment for renal fibrosis.